Forensic appraisal of death due to acute alcohol poisoning: three case reports and a literature review - Hui Wang; Hongmei Xu; Wencan Li; Beixu Li; Qun Shi; Kaijun Ma; Bi Xiao; Long Chen (Oxford University Press, 2020)
Death due to acute alcohol poisoning lacks specific anatomical characteristics, compared with other deaths due to drug poisoning. We report three forensic cases of death from acute alcohol poisoning due to inhibition of the respiratory centre and eventual asphyxia. Blood alcohol concentrations in the three fatalities were 5.28, 3.33 and 3.78 mg/mL, respectively. Lethal doses and blood alcohol concentrations showed differences between individuals. Detailed auxiliary tests besides autopsy were undertaken. These cases show that forensic scientists should exclude other causes of death, combine the autopsy with auxiliary tests, and then make an appraisal.